Russia's nuclear threats in the war against Ukraine: Consequences for the international order, NATO and Germany - Liviu Horovitz; Lydia Wachs (Stiftung Wissenschaft und Politik (SWP), 2022)
Any conflict with a nuclear power like Russia carries the risk that nuclear weapons could be used, and President Vladimir Putin is aggressively exploiting such concerns. With its nuclear threats, the Kremlin is moving away from Russia's doctrine that ascribes a protective role to its nuclear arsenal. In this way, Moscow aims not only to deter Western governments from providing more substantial support to Ukraine, but also to intimidate the Western public. However, as long as NATO does not intervene directly in Ukraine and the Russian regime does not feel existentially threatened, both intentional and unintentional nuclear use remain extremely unlikely. Nevertheless, Moscow's nuclear threats still entail significant negative consequences. If Russia succeeds in using nuclear deterrence to shield an offensive conventional war, this could further destabilise Europe and the global security order.
Keywords: 320